Estudio de factibilidad para la introducción de un yogurt con sabor a guayaba en las comunas 13,14 y 15 en la ciudad de Cali (2012)
When analyzing the market specifically for dairy and yogurt production companies, shows that in recent years the variety of yogurt has focused on its functionality, but the flavors were apparently preserved by the tradition of the fruits its component, taking into account the above this project proposes a feasibility study to launch flavored yogurt Guava with innovative packaging, posing a new trend of diversification of flavor along with functionality, initially in 13,14 and 15 communes of the city of Cali, in the area known as the Aguablanca district. The research makes a market study with reference 13,14 and 15 communes of the city of Cali, identifying the political, legal, economic, technological, environmental, social, demographic and cultural landscape off to achieve a the market to which the new product is intended, then makes an analysis of guava flavored yogurt defining the nutritional benefits it offers in terms of market demand and supply analyzes with their projections, is also the method of collection primary data through a survey of the residents of the three municipalities and the conclusions from the information obtained. Observed market then presents the technical study identifying the raw material for processing, the units to produce, direct and indirect costs of manufacturing, distribution and location of the production plant, and the flow of production and logistics processes , administrative, via an administrative structure with job descriptions, functions, command line and effective communication channels to operate it, as well as the infrastructure is essential for the initiation of the project is also necessary to consider the organizational study where the mission, vision, corporate objectives, the organization chart Deligurt, manuals of procedures and functions of the different legal aspects later charges that directly or indirectly influence the introduction of guava flavored yogurt. Upon completion of a comprehensive study was conducted economic and financial order to determine the feasibility of the project from this perspective using different budgets using accounting methods and financial indicators as the NPV, IRR and payback period of investment among others based to all information that could be obtained and analyze findings and recommendations were generated for the launch of a guava flavored yogurt in 13,14 and 15 communes in the city of Cali.